Fast pH-driven solubilization method of realgar (As4S4) to reduce the toxicity of arsenic (As(III)) for medicinal purposes - Lucic, Bojana; Franciscato, Douglas Santana; Nogueira, Helton Pereira; Gallucci, Lara; Silveira Junior, Alceu Totti; Ismail, Asmaa Mohamed; Robinson, Millie; Dallinger, Teresa; Gutfleisch, Claudia; Kurz, Jochen; Toledo, Maytê; Dias da Silva Ferraz, Jessica; et al. (Advanced science, 2025)
Acute promyelocytic leukemia (APL) accounts for 5-15% of acute myeloid leukemia cases. It is typically characterized by the (15;17) chromosomal translocation, producing the pathogenic retinoic acid receptor (RAR) alpha/promyelocytic leukemia (PML) fusion protein. Recently, remission of APL has been achieved using the first chemotherapy-independent oral drug regimen in anticancer therapy, consisting of all-trans retinoic acid (targeting RARalpha) and the arsenic sulfide realgar (targeting PML). However, clinical adoption of realgar and the characterization of its active breakdown products have been hampered by its poor solubility. Here, a scalable pH/temperature-based process is described that partially mimics gut transition, achieving fast and reproducible solubilization of realgar. Six different spectroscopic and spectrometric techniques are employed to investigate solubilized realgar. Furthermore, it is shown that solubilized realgar targets PML, displaying wider in vitro therapeutic indices and lower off-target effects than arsenic trioxide, the current APL standard of care. Moreover, in line with evidence of an interplay between PML and HIV persistence, solubilized realgar can disrupt HIV latency, the main barrier to an HIV/AIDS cure, in CD4 T cells of people living with HIV. These findings may open avenues for streamlining realgar solubilization and designing less toxic, orally administrable arsenic-based therapies.
Im Titel ist bei (As4S4) die 4 jeweils tiefgestellt, der Ausdruck "As(III)" steht in eckigen Klammern
Online veröffentlicht: 24. April 2025
Gesehen am 09.12.2025